1964
DOI: 10.1139/m64-058
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Chemical Properties of Cell Envelopes of the Extreme Halophile, Halobacterium Cutirubrum

Abstract: In the electron microscope, isolated cell envelopes of the extremely halophilic bacterium, Halobacteriunz cutirubrum, have the same hexagonal surface pattern and roughly the same shape as do intact cells. At different pH values and in different ionic environments the envelopes undergo changes in shape and surface structure similar to those of intact cells. These changes are probably not due to osmotic Dressure. In media of low ionic strennth envelooes disinte~rate. This disintegration appears to involve a t le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

1965
1965
1989
1989

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…These bacteria require high concentrations of salt (1 M to 4 M NaCI) prevent cell lysis, and evidence that the halophilic behavior may be related to an abnormality in membrane structure has emerged from the studies of Kushner, Brown, and 'their co-workers (34)(35)(36)(37), who showed that the requirement for high salt concentrations was also shown by isolated cell envelope preparations, which dissolved when placed in solutions of low ionic strength. These bacteria require high concentrations of salt (1 M to 4 M NaCI) prevent cell lysis, and evidence that the halophilic behavior may be related to an abnormality in membrane structure has emerged from the studies of Kushner, Brown, and 'their co-workers (34)(35)(36)(37), who showed that the requirement for high salt concentrations was also shown by isolated cell envelope preparations, which dissolved when placed in solutions of low ionic strength.…”
Section: Membraine Lipidãmentioning
confidence: 99%
“…These bacteria require high concentrations of salt (1 M to 4 M NaCI) prevent cell lysis, and evidence that the halophilic behavior may be related to an abnormality in membrane structure has emerged from the studies of Kushner, Brown, and 'their co-workers (34)(35)(36)(37), who showed that the requirement for high salt concentrations was also shown by isolated cell envelope preparations, which dissolved when placed in solutions of low ionic strength. These bacteria require high concentrations of salt (1 M to 4 M NaCI) prevent cell lysis, and evidence that the halophilic behavior may be related to an abnormality in membrane structure has emerged from the studies of Kushner, Brown, and 'their co-workers (34)(35)(36)(37), who showed that the requirement for high salt concentrations was also shown by isolated cell envelope preparations, which dissolved when placed in solutions of low ionic strength.…”
Section: Membraine Lipidãmentioning
confidence: 99%
“…Gram-negative bacteria contain almost exclusively saturated and monounsaturated C16 and C18 fatty acids (59,60). Membranes of Halobacterium cutirubrum, a bacterium that grows only in solutions of sodium chloride that are at least 3M, dissolve in distilled water (67). Escherichia coli strain B may contain no unsaturated fatty acids (61).…”
Section: Chemical Composition Of Membranesmentioning
confidence: 99%
“…The cells lack the rigid murein sacculus and an outer membrane typical of Gram-negative eubacteria. Instead, halobacteria are surrounded by a single layer of hexagonally arranged protein subunits [7][8][9][10][11][12]. Xray diffraction studies as well as electron microscopy of thin sections were interpreted to demonstrate the existence of two protein layers outside the cytoplasmic membrane, separated by a 'periplasmatic space' [13,14].…”
Section: Introductionmentioning
confidence: 99%